Peru : Second Review Under the Stand-By Arrangement; Staff Report; Staff Statement; Press Release News Brief on the Executive Board Discussion; and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report ;, 2008)
Peru's macroeconomic policies continue to be strong under the Stand-By Arrangement (SBA). Executive Directors appreciated the implementation of policies to entrench macroeconomic stability, lower poverty, and lessen vulnerabilities, and also emphasized the need to maintain a prudent fiscal policy stance, implement structural reforms, solidify the fiscal framework, and accelerate the implementation of the antipoverty strategy. They also stressed the need to entrench greater exchange rate flexibility, strengthen the inflation, preserve a prudent role for public banks, and enhance the business environment.